KESEIMBANGAN ANTARA DISIPLIN KERJA DAN KOMPENSASI DENGAN PRODUKTIVITAS KERJA KARYAWAN DI PERUSAHAAN PELAYARAN - Honny Fiva Akira Sembiring; Dedeng Wahyu Edi (Institut Transportasi dan Logistik Trisakti, 2016)
Human Resources of better known as the workforce is one of important factor that must be considered by the company in order to achieve its goals. It is needed the company’s ability to manage resources in a planned, especially human resource as the company’s executive power to generate power operational effectiveness and efficiency in any activities of the company. One factor that is important to note the company’s management in an effort to improve the quality of human resources, so the impact of increased labor productivity is a factor of discipline and compensation.The purpose of this study was to examine the relationship of discipline and compensation to labor productivity. The study design using hypothesis testing with multiple linear regression analysis method, to determine the magnitude of the relationship of independent variables on the dependent variable. In this study , data collection is done by spreading the census questionnaire to 36 employees of PT. Marindo Jaya Abadi, which of 36 questionnaire distributed a total of 36 answered in full by the employee and can be analyzed using multiple linear regression. The results of this study concluded that the first, the discipline has a strong relationship with work productivity. Second, compensation has a strong relationship with work productivity. Third, discipline and motivation jointly strong associated with work productivity.